Methylmercury disruption of embryonic neural development in Drosophila - Rand, Matthew D. (2009)
Methylmercury (MeHg) is a potent environmental neurotoxin that preferentially targets the developing embryonic nervous system. While a number of cytotoxic mechanisms of MeHg have been characterized in differentiated cells its mode of action in the developing nervous system in vivo is less clear. Studies in primate and rodent models demonstrate aberrant cell migration and disorganized patterning of cortical layers in the brain following MeHg exposure. However, defining the molecular and cellular pathways targeted by MeHg will require more genetically accessible animal models. In this study, we instigate a method of in vitro MeHg exposure using Drosophila embryos. We demonstrate dose-dependent inhibition of embryonic development with MeHg revealed by a failure of embryos to hatch to the larval stage. In addition, we document definitive phenotypes in neural development showing abnormalities in neuronal and glial cell patterning consistent with disrupted migration. As well, we observe pronounced defects in neurite outgrowth in both central and peripheral neurons. Ectopic expression of the Nrf2 transcription factor in embryos, a core factor in the antioxidant response element (ARE) pathway, enhances embryonic development and hatching in the presence of MeHg, illustrating the power of this model for investigation of candidate MeHg tolerance genes. Our data establish a utility for the Drosophila embryo model as a platform for elucidating MeHg sensitive pathways in neural development.